A tradição e a renovação dos ministérios laicos no contexto Pós-Vaticano II: uma reflexão na perspectiva de Yves Congar - Pereira, Anderson Costa (2023)
This dissertation investigates the renewal of lay ministries in the post-Vatican II context from the perspective of the French theologian Yves Congar (1904-1995). The study addresses the question of how the theological understanding of Tradition and ministries, in light of this theologian's thinking, can promote a more inclusive and collaborative participation of the lay faithful and a ministerial renewal in the life of the Church. Thus, the objective of this text is to analyze the concepts of Tradition and ministries in their historical and theological aspects and how they can be applied to ministerial renewal in the post-Vatican II context. To achieve this objective, a bibliographical investigation was carried out that seeks to clarify the issue based on already published theoretical references, but above all on the theological assumptions of Yves Congar. The dissertation is structured as follows: in the first chapter, a theological approach to the concept of Tradition in Congar's thought is presented; in the second chapter, historical and theological questions about lay ministries are discussed; in the third chapter, as a synthesis of the previous chapters, theological-pastoral parameters on the renewal of lay ministries in the post-conciliar context are addressed. Finally, the conclusions highlight the contributions, limits and new paths of ministries in the Church, admitting that by establishing new ministries, the Church can promote greater active participation of lay people in ecclesiastical life, diversifying roles and responsibilities within the community. This contributes to the greater vitality of the Church